The yellow rose : racial stratification in a Mexican American community - Verdugo, Richard R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"The volume examines the effect racial stratification had on the economic and social lives of Mexican Americans and Anglo residents in a community that was majority Mexican American. The impact was felt economically as the community was a one-crop economy, and also in creating social disharmony between Mexican Americans and the politically and economically dominant Anglo community. This is an historical study since it is based on a survey conducted in 1969. It is one of only a few complete Mexican American community studies ever conducted."-- Provided by publisher.
Keywords: Mexican Americans -- Texas -- Fabens -- Social conditions -- 20th century.; Mexican Americans -- Texas -- Fabens -- Race relations -- 20th century.; Mexican Americans -- Texas -- Fabens -- Economic conditions -- 20th century.; Social stratification -- Texas -- History -- 20th century.; Race discrimination -- Texas -- History -- 20th century.; Social surveys -- Texas -- El Paso County.; Texas -- Ethnic relations -- Case studies.; Fabens (Tex.) -- Social conditions.; Fabens (Tex.) -- Economic conditions.; Fabens (Tex.) -- History, Local.; elektronické knihy; Case studies.; Social Science -- Cultural & Ethnic Studies -- American -- Hispanic & Latino Studies.; Ethnic groups and multicultural studies.; Ethnic studies.; United States of America, USA.; Relating to Latin, Hispanic American people.; electronic books